KEMAMPUAN PENDAMPING LOKAL PADA PENGELOLAAN DANA DESA (Studi di Desa Ambia Utara Kecamatan Essang Selatan Kabupaten Kepulauan Talaud) - MANGOLE, SARTIKA SANGIANG; POSUMAH, JOHNNY; PALAR, NOVIE (JURNAL ADMINISTRASI PUBLIK, 2021)
The purpose of this study was to determine the ability of local assistants to manage village funds in NorthAmbia Village, South Essang District, Talaud Islands Regency. The research method used is descriptivequalitative. In this study the ability of village local assistants was measured by technical skills, human skills,conceptual skills and management skills. Research informants were village assistants, sub-district villagelocal assistants, village government and the community. The data collection techniques used wereobservation, interview and documentation. Based on the results of the study, it was found that the villageassistants were still not maximal in carrying out their duties. So the authors recommend that further improvetechnical skills, human skills, conceptual skills and management skills in carrying out their duties as villageassistants.Keywords: Ability, Village Facilitators, Village Fund Management